Influence of the seismic vertical component on the dynamic response of RC highway bridges with partially restrained seismic isolation - Nanclares, Germán Aníbal (2025)
This study provides an in-depth assessment of the influence of the Seismic Vertical Component (SVC) on the seismic behavior of continuous reinforced concrete (RC) highway bridges retrofitted with Partially Restrained Seismic Isolation (PRSI). Focusing on a representative isolated bridge, the study utilizes a detailed three-dimensional numerical model to simulate nonlinear material behavior and structural collapse mechanisms. The seismic performance of the PRSI-rehabilitated RC bridge is assessed by analyzing its dynamic response under major earthquake records, considering both the presence and absence of the SVC. The response of the original unrehabilitated bridge serves as a comparison reference. The results reveal a brittle collapse mechanism influenced by the SVC, and significant alterations in axial forces within the central column. In summary, both the SVC and the friction coefficient of the isolation device exert substantial influence on seismic performance.